Hormesis in Health and Disease: Molecular Mechanisms - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Hormesis was initially defined as a phenomenon where a small dose of harmful agent exposure to living organisms gives beneficial effects. The dose and time of this ‘tress’ exposure has become the object of investigation across the broad range of biomedical studies.CONTENT: Hormesis characterized by the biphasic dose-effect or time-effect relationship for any substance. Some hormetic mechanisms performed biological plasticity, involve oxidative damage which instead induce antioxidant enzyme production in various cells. Early-life stress can increase resilience in later life and lack of stress can lead to vulnerability. Many stressors like dietary factors and natural environmental toxins can be occupied for healthy growth or homeostasis, which exemplifies how illness is the doorway to health.SUMMARY: Hormesis reconcile many paradoxical phenomena exert opposite effects of the same substance, either a xenobiotic or an endogenous substance, a hormone or a metabolite, a genetic manipulation or an epigenetic alteration, an experimental intervention or a natural event. Human bodies are highly adaptive. A resilient body would be resulted after the ‘training’. In this review, we will elucidate the hormesis’ definition, mechanisms and pathways, and also how hormesis impacts in human health and lifespan.KEYWORDS: biphasic, cell signaling, dose response, hormesis, preconditioning